The Impact of Cloud Computing on Supply Chain Management in Small and Medium Enterprises (SMEs) - Dia Ragasari; Adelia Riana Dewi (International Journal Multidisciplinary Science, 2026)
Small and Medium Enterprises (SMEs) are increasingly adopting cloud computing to optimize their supply chain management (SCM) processes. While cloud computing has shown positive results in large enterprises, its impact on SMEs remains less explored. SMEs face unique challenges, including limited resources and technical expertise, making it essential to understand the specific benefits and obstacles they encounter when adopting cloud-based SCM solutions. Objective: This research aims to investigate the impact of cloud computing on SCM in SMEs, focusing on the benefits, challenges, and overall performance improvements brought about by cloud adoption. The study seeks to fill the gap in existing literature by addressing the specific needs and barriers faced by SMEs. Methodology: A mixed-methods approach was used, combining quantitative surveys and qualitative semi-structured interviews. The survey targeted SMEs that adopted cloud-based SCM solutions, collecting data on perceived benefits, challenges, and performance metrics. In-depth interviews were conducted with key decision-makers to explore their experiences and strategies. Data analysis included descriptive statistics and regression analysis for the quantitative data, and thematic analysis for the qualitative data. Findings: The study found that 85% of SMEs adopted cloud-based SCM systems, with notable benefits including cost reduction (68%), improved efficiency (70%), and better collaboration (60%). However, challenges such as data security concerns (72%) and integration with legacy systems (58%) were prevalent. Despite these challenges, SMEs reported a 17% reduction in operational costs and an 18% improvement in inventory turnover. Implications: Cloud computing offers significant potential to improve SCM in SMEs, though addressing barriers like data security and system integration is crucial for full adoption. Cloud service providers should offer more secure and customizable solutions for SMEs, and policymakers should consider initiatives to support their digital transformation. Originality and Contribution: This study adds value by focusing on SMEs and providing new insights into the unique barriers they face in adopting cloud computing for SCM. The research offers practical recommendations for both SMEs and cloud providers and contributes a novel framework for understanding cloud adoption in this sector.